KONSEP DASAR ARSIP KARYA SENI, EPHEMERA, DAN WARISAN BUDAYA - Atika Pikriyani Ramdhani; Muhammad Aditya Rachman (Nusadaya Journal of Multidiciplinary Studies, 2026)
possess historical, cultural, and informational value. Along with the development of archival science, the concept of archives has expanded beyond administrative records to include various records of human activities that hold authentic and long-term value. This article aims to examine the fundamental concepts of art archives, ephemera, and cultural heritage, as well as to explain the relationship among these three elements from an archival perspective. This study employed a descriptive qualitative approach using a literature review method. Data were collected from relevant scholarly articles and analyzed through identification, classification, comparison, and synthesis of previous research findings. The results indicate that art archives and ephemera constitute significant components of cultural heritage due to their informational, evidential, historical, and cultural values, making systematic management essential. Furthermore, digitalization has become an important strategy for supporting preservation efforts and improving public access to cultural archives in the digital era. Therefore, archival management supported by standardized description, digital technology, and collaboration among archives, museums, libraries, and cultural institutions is essential to ensure the sustainability of information and the preservation of cultural heritage for future generations.